Specific antibody titer decay in neonates prenatally exposed to Toxoplasma gondii and their mothers - Serena Salomè; Claudia Grieco; Pasquale Fabio Barra; Eleonora Capone; Fiorentino Grasso; Francesca Carraturo; Pasquale Dolce; Paola Salvatore; Letizia Capasso; Francesco Raimondi (Italian Journal of Pediatrics, 2022)
Abstract Background For infants exposed in utero to Toxoplasma gondii, current guidelines recommend monitoring the specific antibody titer until 12 months of age. In this study, we investigated the antibody titer decay in the mother-infant dyad. Methods This is a single center, population-based cohort study of neonates referred for prenatal exposure to Toxoplasma gondii from January 2014 to December 2020. All infants underwent clinical, laboratory, and instrumental investigation for at least 12 months. Results A total of 670 eligible neonates were referred to the Perinatal Infection Unit of the University Federico II of Naples. 636 (95%) completed the serological follow up until 12 months. Specific IgG antibodies negativization occurred in 628 (98.7%) within 5 months. At 9 and 12 months, all patients had negative IgG. An initial neonatal IgG antibody titer ≥ 200 IU/ml was associated with a longer time to negativization (184 [177.5;256] days when above threshold vs. 139.5 [101;179] days when below it; p < 0.001). Maternal IgG antibody titer ≥ 200 IU/ml at childbirth was also associated to delayed time to negativization in the infant (179 [163;184] days above the threshold vs 125 [96.8;178] days below it; p < 0.001). Specific antibody negativization was irreversible in all patients. Conclusions Lower anti-Toxoplasma antibody titers detected at birth in the mother-infant-dyad lead to an earlier and irreversible negativization. This information allows for customisation of the infant follow up program and avoids invasive and expensive tests.